Marketing Strategy of Shrimp Crackers Reviewed From Sharia Marketing - Naning Fatmawatie; Nilna Fauza; Sri Anugerah Natalina (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
Activities in the marketing strategy include comprehensive and interrelated planning in the marketing aspect, which provides instructions for the activities to be carried out in order to achieve the marketing objectives of a particular company. Sharia marketing is a business activity that uses a marketing strategy based on business values contained in the Quran and Hadith. The purpose of this study was to determine the marketing strategy and marketing strategy of prawn crackers in terms of sharia marketing. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The data analysis technique used is descriptive analysis method. The results of this study indicate that: The marketing strategy of UD. Devi Putri by applying the marketing mix. Even though in marketing it still uses traditional or face to face promotions. In addition, it also promotes it through the existing packaging wrapped in prawn crackers at UD. Devi Putri, namely No Hp, P-IRT and halal certificate from MUI. UD. Devi Putri was able to synergize the sharia marketing perspective analyzed using the marketing mix and sharia characteristics, namely theistic (rabbaniyah), ethical (akhlaqiyyah), realistic (al-waqi'iyah) and humanistic (al-insaniyyah).